The Risks and Rewards of Sexual Debut - Golden, Rachel Lynn (Dev Psychol, 2016)
The sex-positive framework of sexual development hypothesizes that healthy sexual experiences can be developmentally appropriate and rewarding for adolescents despite the risks involved. Research has not examined whether risky behaviors and rewarding cognitions actually change with sexual debut at a normative or late age. This study measured the longitudinal impact of sexual debut using 7 waves of data from 88 male and 86 female adolescents from a Western U.S. city who were in the 10(th) grade at the study’s onset. We used piecewise growth curve analyses to compare behavior and cognitions before and after first sexual intercourse for those whose debut was at a normative or late age. These analyses revealed that sexual debut was related to rewards including increases in romantic appeal, and sexual satisfaction. In addition, internalizing symptoms declined over time after sexual debut, and substance use grew at a slower rate after sexual debut. We also examined whether differences existed among those whose debut was at an early, normative, or late age. Linear growth curve analyses revealed early sexual debut was related to risks, such as greater substance use, more internalizing and externalizing symptoms and lower global self-worth. Rewards associated with an early debut included greater romantic appeal, dating satisfaction (males only), and sexual satisfaction (males only). Although there are some inherent risks with sexual activity, the results suggest that sexual debut at a normative or late age is also associated with a decrease in some risks and increase in rewards.